Online information problem solving. An overview of the strategies used by 8- to 13-year-old students in French-speaking Belgium - AUDREY KUMPS; GAËTAN TEMPERMAN; BRUNO DE LIÈVRE (Metaichmio Publications, 2022)
In French-speaking Belgium, one of the new missions of the teacher will be to develop learners' information skills, namely their skills in searching, evaluating, and using information on the web. But do teachers know the strategies used by their students to adapt their teaching interventions? The aim of this study is to provide an overview of the different strategies used by 8 to 13 year old students when searching online. To achieve this objective, we use the IPS-I model and a methodology based on the analysis of the actual practices of 260 primary and secondary school students. Our results show that almost all of the students tested are novices in information retrieval. They do little or no research planning, use basic strategies, never check the reliability and relevance of the information they find and do not cite the sources used. These findings, in the light of previous empirical research on online search behaviour, allow for reflection on educational interventions and provide recommendations for educational practice.